2022
DOI: 10.1155/2022/8666724
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated CEA and CA 19-9 Levels within the Normal Ranges Increase the Likelihood of CRC Recurrence in the Chinese Han Population

Abstract: Objective. This study aimed to determine if variations in the expression profiles of CA 19-9 and carcinoembryonic antigen (CEA) within the reference range could serve as possible biomarkers for postoperative CRC recurrence. Method. This retrospective cohort investigation enrolled 2,596 cases of CRC that received curative surgery. Serum CEA/CA 19-9 were measured through chemiluminescence immunoassay (CLIA). Results. During follow-up (median follow-up = 5.2 years), in total, 837 patients experienced recurrence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Furthermore, in the validation cohort, C1 status was associated with an almost 50% increase in overall and cancer-specific mortalities. These findings are consistent with those of previous studies and strongly suggest that serum CEA level can serve as an independent prognostic factor in patients with CRC ( 5 , 10 , 19 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in the validation cohort, C1 status was associated with an almost 50% increase in overall and cancer-specific mortalities. These findings are consistent with those of previous studies and strongly suggest that serum CEA level can serve as an independent prognostic factor in patients with CRC ( 5 , 10 , 19 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…It is highly expressed in CRC cells and is a potential target for CRC treatment. 136 , 137 In a phase I clinical trial on CEA, three mCRC patients received the CAR-T treatment, and their serum CEA levels decreased significantly. One patient had lung metastasis and liver metastasis, and all patients had severe colitis.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of CEA or CA 19-9 both indicated higher tumor recurrence in patients, which was applied to diagnose and provide guidelines for CRC patients. ( 19 ) Kasanga et al ( 20 ) reported the combination of CEA, CA 19-9, and Hsp90α together could help to distinguish early-staged CRC. They found the levels of Hsp90α were significantly higher in advanced CRCs (stage III and IV) compared to CRC I and CRC II because they could promote cell proliferation and cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%